Recovery from COVID-19: a 12-month follow-up study on cardiorespiratory fitness and pulmonary function - Goulart, Cássia da Luz; Maldaner, Vinícius; Alves, Carla Cristina de Araújo; Milani, Mauricio; Milani, Juliana; Gonçalves da Costa, Ana Clara; Alves, Marcela Lopes; Borges, Robson Fernando; Sobral, Claudia Cristina Conde Holanda; Moraes, Letícia de Araújo; Coutinho, Jean Carlos; Gomes, Nádia Oliveira; et al. (Frontiers in Cardiovascular Medicine, 2025)
Introduction and aimLong COVID, characterized by persistent symptoms after acute infection, poses a major public health challenge. Understanding its long-term effects is crucial, particularly in relation to cardiorespiratory recovery. This study aimed to assess changes in cardiorespiratory fitness (CRF) and pulmonary function (PF) over 12 months following acute COVID-19, addressing a significant gap in current knowledge about the disease's lasting impact.MethodsThis prospective cohort study included 29 individuals previously diagnosed with post-acute COVID-19. The baseline data were collected during the acute phase of infection. Participants underwent clinical evaluation, cardiopulmonary exercise testing (CPET), spirometry, and maximal inspiratory pressure (MIP) measurement at baseline and again after 12 months.ResultsAfter one-year, significant improvements were observed across several CPET parameters, including VE/MVV ratio (Cohen's D = 0.66), peak oxygen uptake (VO2peak) in both absolute and relative terms (ml/min: d = 0.67; and ml/kg/min: d = 0.45), oxygen uptake efficiency slope (OUES; D = 0.47) and a reduction in VE/VCO2 slope (D = 0.80). Pulmonary function improved with increases in % predicted forced expiratory volume in 1 s (FEV1; d = 0.67) and forced vital capacity (FVC; D = 0.67). MIP improved significantly (D = 0.67), and the prevalence of inspiratory muscle weakness decreased from 20.7% at baseline to 3.5% at follow-up.ConclusionDespite the severity of their initial illness, patients demonstrated substantial recovery in CRF, PF, and inspiratory muscle strength over 12 months.